Perceptions of the Department of Family and Community Medicine, University of the Philippines-Philippine General Hospital Residents and Faculty on the attributes of an effective clinical teacher in family medicine training - Sabra, Ahmed S.
Participants: UP-PGH DFCM residents (52) and faculty members (32) currently employed by January 2008. Objectives: The general objective of this study is to describe the perceptions of UP-PGH DFCM residents and faculty members on the attributes of an effective clinical teacher. The specific objectives are: 1) To describe the socio-demographic profile of UP-PGH DFCM residents and faculty members and correlate to the perceptions of effective clinical teacher. 2) To compare the perceptions of UP-PGH DFCM residents and faculty members of attributes most and least important for effective clinical teaching. Design: Descriptive study. Instrumentation: Buchel and Edwards 2005 Questionnaire on Attributes on Effective Clinical Teaching in English, Key Informant Interview in English, Focus Group Discussion in English. Data Collection Methods: The study was explained in residents and faculty conference and for a Questionnaires were later distributed to all the faculty members and residents. Collection of the answered questionnaires was done thrice. The Key Informant Interview and Focus Group Discussions were done by invitation and availability of interviewees or respondents. Data Analysis: Completed Questionnaires were coded and the data were computed using SPSS. Text analysis was done on the KII and FGD data. Frequencies were determined from the different attributes in references to the different sociodemographic profile. The three most important attributes perceived to be most important in clinical teaching were knowledge base, role modelling and enthusiasm. The three least important were scholarly activity, availability and organizational skills. Conclusion: Disagreements and agreements of opinions on the perceptions of effective clinical teaching were noted, particularly on whether it is more of the content or the method of teaching. Knowledge base, the top most important, refers to the content; which can be effectively delivered through role modelling and with enthusiasm, which are methods of teaching. In general, most of the perceptions of the resident and faculty member respondents were similar. These were validated with the KII and FGD. A dissonance however existed between the perception and reality of availability as an important attribute. Perceived as a least important attribute, it however remains an important factor at the organizational level. There are no notable difference in other sociodemographic profiles except for the higher preference of community-based consultants for the attributes of enthusiasm and availability. An interplay of these attributes were noted which should be considered if a competency-based system is to be established using the attributes.